An overview of Mechanical properties of Nano-composites - Mohammed Ridha H .Alhakeem (Information Technology and Science (ITScience), 2022)
Due to the anisotropic, heterogeneous structure, and advanced mechanical properties of these materials combined with the size effects in micromachining, micromachining of nanocomposites is thought to be a challenging operation. In terms of high cutting force, poor surface quality, and rapid tool wear, it results in worse machinability. The first of these two parts of this review paper will provide a thorough overview of the mechanical characteristics of diverse nanocomposites, while the second part will concentrate on the micro-machinability of these nanocomposite materials.